Cultural landscape as heritage: proposals for Ukraine from the experience of certain European countries - Polyvach, Kateryna (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2023)
Formulation of the problem. Ukraine has a vast and uniquely diverse cultural landscape potential. However, the state of the landscapes, which has long been a matter of public concern, has deteriorated many times over as a result of russia's full-scale armed aggression against Ukraine. At the same time, Ukraine is far behind in implementing the commitments made by the European and international community in a number of international documents on the preservation of cultural landscapes.The purpose of the article. The purpose of this publication is to develop proposals for the implementation of the concept of cultural landscape in the field of protection and preservation of cultural and natural heritage on the basis of fulfilling Ukraine's relevant international obligations and introducing the best mechanisms and practices of European countries.Methodology and results. The research methodology is based on a descriptive qualitative and comparative approach, which made it possible to reveal the peculiarities of the experience of preserving the cultural landscape as a heritage in certain EU countries - representatives of the “old Europe” (Italy and Spain), post-socialist (Poland, Slovakia, Czech Republic) and post-Soviet (Latvia and Lithuania) space. The European experience was studied through the prism of meeting the requirements of the European Landscape Convention and the possibilities of its practical application in Ukraine.The analysis of examples of practical implementation of the concept of cultural landscape by European countries in comparison with domestic practice in Ukraine made it possible to identify the main problems in this area and to outline indicative directions of a possible strategy for their solution, the main mechanisms, tools and specific measures for their implementation.The first step in the development of such a strategy could be the development and adoption by government decree of a National Action Plan for the Protection and Preservation of the Cultural Landscape Heritage of Ukraine. The overall goal of this plan for the next 5-10 years should be to ensure the protection, preservation and careful use of the country's cultural landscapes by: bringing the country's legislation into line with the EU system of legal and regulatory standards for landscape protection, regulation and planning; taking these issues into account in the formulation and implementation of state cultural, environmental and urban planning policies and including them as an integral part of the strategy for Ukraine's post-war reconstruction; raising public awareness and involving communities.Scientific novelty and practical significance. The novelty of the study is the identification of the main areas of action for the protection and preservation of the cultural landscape heritage of Ukraine and the development of concrete proposals for their filling with appropriate measures.Acknowledgement. The research is financed by the European Union NextGenerationEU from the funds of the Recovery and Resilience Plan mechanism within the project "Scholarships for outstanding researchers threatened by the military conflict in Ukraine" No. 09І03-03-V01-00021. This article is one of the results of the research within the framework of grant no. 2/0043/23 "Identification of landscape diversity and its changes in Slovakia based on remote sensing data in the context of the European Green Deal" supported by the Slovak Scientific Grant Agency VEGA.